Health outcomes in the colombian elderly population with amputations: a secondary analysis of the SABE survey - Pinilla-Aldana, Thalía L. (2023)
Objective. To describe the factors associated with amputations in the Colombian elderly population (>60 years) as evaluated in the 2015 SABE Survey with its possible adverse health related outcomes. Materials and methods. Cross-sectional, retrospective and analytical study consisting of a secondary analysis of the SABE (Health, Well-being and Aging) Colombia 2015 survey. Excluding factors were people who required a substitute informant during the interview, people without amputations and those with upper and lower limb amputations simultaneously. The dependent variables were the adverse health outcomes in older people with amputations (depressive symptoms, mobility problems, poor self-perception of health, disability discrimination, falls in the last year, whether or not help was needed in the last fall, and hospitalizations in the last year). Both descriptive and bivariate analysis as well as multivariate logistic regression were performed. Results. The sample was of 278 elderly, 77.34% were men, with a mean age of 70 ± 11 years. Variables such as male sex (OR 3.62 95%CI 1.82-7.19, p<0.001) and arterial hypertension (OR 3.45 95%CI 1.77-6.71, p<0.001), were positively associated with upper limb amputations. Likewise, for lower limb amputations, a positive association was found with diabetes (OR 7.78 95%CI 3.78-16.02, p<0.001). However, there was a negative association with male sex (OR 0.27 95%CI 0.14-0.55, p<0.001) and arterial hypertension (OR 0.29 95%CI 0.15-0.56, p<0.001). Conclusion. In people over 60 years of age, factors such as being a man and having high blood pressure are associated with upper limb amputations; counterwise, diabetes is associated with lower limb amputations.